2017
DOI: 10.1002/adfm.201702180
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Nucleation for Halide Perovskite Thin Films with Large and Uniform Grains

Abstract: Halide perovskite materials have come to the forefront of optoelectronics recently owing to their excellent light absorbing and emitting properties. Despite their excellent properties there are still problems that need to be overcome such as short operating lifetimes, and an observed hysteresis behavior in their current-voltage characteristics. It is found that these chal lenges could be overcome by developing a deterministic nucleation process using gold as a nucleation promoter to control the grain size of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 52 publications
4
35
0
Order By: Relevance
“…The results are shown in Figure 8a,b. [20] Figure 8d presents the variation of the normalized PCE for the unsealed PVSCs stored in N 2 -filled glove box and humid air (RH = 50%). According to Figure 8a www.advenergymat.de www.advancedsciencenews.com and MAPbI 3 (14.14°) was calculated and displayed in Figure 8c as a function of storage time in humid air (RH = 50%).…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown in Figure 8a,b. [20] Figure 8d presents the variation of the normalized PCE for the unsealed PVSCs stored in N 2 -filled glove box and humid air (RH = 50%). According to Figure 8a www.advenergymat.de www.advancedsciencenews.com and MAPbI 3 (14.14°) was calculated and displayed in Figure 8c as a function of storage time in humid air (RH = 50%).…”
Section: Resultsmentioning
confidence: 99%
“…24 Furthermore, smart strategies have been reported to fabricate large-sized single-crystal thin lms. [25][26][27] However, directly extending these methods [28][29][30][31] to 2D growth is difficult. [32][33][34][35][36][37][38][39][40] The existing growth methods for (PEA) 2 PbBr 4 single crystals mainly involve converting polycrystalline thin lm to single-crystal nanoplates.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we compared the stability of the unencapsulated control device based on 100% toluene and the device based on 50% toluene under ambient air condition with 22°C and RH ≤ 30% for about 200 h. As shown in Figure 8, we found that the device adopted 50% toluene exhibited excellent stability with PCE retaining 78% of its initial value after 200 h. The value of V OC remained almost unchanged, and FF and J SC only slightly decreased to 95% and 82% of their original value. While for the control device with 100% toluene anti-solvent, the PCE value dramatically decayed to 52% of its initial value with the values of J SC , FF, and V OC all dropping dramatically during 200 h. The morphology of perovskite films has a very important influence on their stability, especially in the ambient air [55][56][57][58][59]. Previous reports have shown that the stability for the dense perovskite films with larger grain size is significantly better than that of low-quality films.…”
Section: Resultsmentioning
confidence: 99%